2018
DOI: 10.1155/2018/6917958
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma, Hydroxyapatite, and Chitosan in the Bone and Cartilaginous Regeneration of Femoral Trochlea in Rabbits: Clinical, Radiographic, and Histomorphometric Evaluations

Abstract: The aim of this study was to evaluate the trochlear bone and cartilaginous regeneration of rabbits using the association of PRP, chitosan, and hydroxyapatite. Hole was made in rabbit troches, one hole in each animal remained empty (group C), and one was filled by a combination of PRP, chitosan, and hydroxyapatite (group T). Clinical-orthopedic, radiographic, and histomorphometric evaluations were performed. Clinical-orthopedic evaluation showed lameness of two members of the T group and one member of group C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…And the result agrees with Sequando et al, 2018 and Shwu et al, 2009 that used the mixture of chitosan and PRP with other CASO4 and showed more bone formation compared with chitosan alone [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…And the result agrees with Sequando et al, 2018 and Shwu et al, 2009 that used the mixture of chitosan and PRP with other CASO4 and showed more bone formation compared with chitosan alone [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…They hypothesized that Chitosan/PRP reside for several weeks in vivo, in contrast to PRP which is quickly degraded. Segundo et al 40 in their study on surgically created cartilage defects in rabbit knees noted that composite base of PRP, hydroxyapatite and chitosan promoted better bone healing and cartilage healing compared to control. There is encouraging in vitro and in vivo evidence that PRP can be used with biomaterials to enhance their effect, however whether this can be translated to actual clinical scenarios remains to be seen.…”
Section: Biomaterial Scaffolds and Prpmentioning
confidence: 99%
“…The production of bioceramic implants that allow its association seems to be the most efficient method of its use, its longer time of biodegradation and its performance in a more specific step of the bone repair compensated by the properties of other polymers, these associations have been showing good results (Segundo FA de et al, ).…”
Section: Resultsmentioning
confidence: 99%